Physiological profile of male competitive and recreational surfers - Furness, J.; Hing, W.; Sheppard, J. M.; Newcomer, S.; Schram, B.; Climstein, M. (The Journal of Strength and Conditioning Research, 2018)
Surfing consists of both high- and low-intensity paddling of varying durations, using both the aerobic and anaerobic systems. Surf-specific physiological studies lack adequate group sample sizes, and VO2peak values are yet to determine the differences between competitive and recreational surfers. The purpose of this study was therefore to provide a comprehensive physiological profile of both recreational and competitive surfers. This multisite study involved 62 male surfers, recreational (n = 47) and competitive (n = 15). Anthropometric measurements were conducted followed by dual-energy x-ray absorptiometry, anaerobic testing and finally aerobic testing. VO2peak was significantly greater in competitive surfers than in recreational surfers (M = 40.71 ± 3.28 vs. 31.25 ± 6.31 ml/kg/min, p < 0.001). This was also paralleled for anaerobic power (M = 303.93 vs. 264.58 W) for competitive surfers. Arm span and lean total muscle mass was significantly (p = 0.01) correlated with key performance variables (VO2peak and anaerobic power). No significant (p = 0.05) correlations were revealed between season rank and each of the variables of interest (VO2peak and anaerobic power). Key performance variables (VO2peak and anaerobic power) are significantly higher in competitive surfers, indicating that this is both an adaptation and requirement in this cohort. This battery of physiological tests could be used as a screening tool to identify an athlete's weaknesses or strengths. Coaches and clinicians could then select appropriate training regimes to address weaknesses.